Prototype E-Order pada Restoran Bebek Goreng Haji Yogi Menggunakan Metode PIECES - Ratna Mutu Manikam; Muhammad Ardiyansah (Jurnal Ilmiah FIFO, 2019)
Restoran Bebek Goreng Haji Yogi adalah suatu usaha restoran yang berkembang Bebek Goreng Haji Yogi Restaurant is a restaurant business that develops in the West Jakarta area. The fried haji yogi duck restaurant serves a variety of menus with the main ingredients of duck meat. During this time, the system that runs in restaurants still uses notes of paper on consumer orders. Losing sheet paper transactions will have an impact on not fulfilling consumer orders and will worsen service. The application of a computerized system at Bebek Goreng Haji Yogi Restaurant is needed to provide effective ordering services to customers and make it easier to make reports. The analytical method used uses the pieces and supporting software methods to design using PHP, MySQL and balsamiq programming languages. The aim is to increase the effectiveness of orders to customers. So that the E-Order service information system can simplify ordering and minimize customers in queuing for food orders so they can minimize data error in recording product sales transaction data.